2021
DOI: 10.1007/s12144-021-02122-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between need for cognition and adolescents’ creative self-efficacy: The mediating roles of perceived parenting behaviors and perceived teacher support

Abstract: Drawing on social cognitive theory, need for cognition might have a significant influence on adolescents' creative self-efficacy. However, no studies, to date, have investigated this relationship. To address this gap in the literature, this study used a 3-year longitudinal design to investigate the effect of need for cognition on adolescents' creative self-efficacy. Moreover, to better understand this effect, we also investigated the mediating roles of perceived parenting behaviors and perceived teacher suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Later studies also indicated that an authoritative parenting style was positively related to self-efficacy (Masud et al, 2016;Llorcamestre et al, 2017). Importantly, there was evidence directly showing that perceived parental support was linked with heightened creative self-efficacy (Gralewski and Jankowska, 2020;Chen et al, 2021). Considering the above, it seems reasonable that parental responsiveness, characterized by attentive, warm reactions toward children's needs to foster individuality, self-regulation, and self-assertion, can facilitate creative self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies also indicated that an authoritative parenting style was positively related to self-efficacy (Masud et al, 2016;Llorcamestre et al, 2017). Importantly, there was evidence directly showing that perceived parental support was linked with heightened creative self-efficacy (Gralewski and Jankowska, 2020;Chen et al, 2021). Considering the above, it seems reasonable that parental responsiveness, characterized by attentive, warm reactions toward children's needs to foster individuality, self-regulation, and self-assertion, can facilitate creative self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires included demographic questions, as well as measures assessing the students' AM, CSE, and their parents' parenting behaviors (autonomy support and behavioral control). Prior studies adopting these scales in senior primary school students and adolescents have revealed good reliability and validity, and these measurements have been shown to be used among Chinese samples (Chen et al, 2021(Chen et al, , 2023Cheung et al, 2016;Li et al, 2015; G. R. Liu et al, 2013;Ren et al, 2017;Ren & Zhang, 2023; H. P. Zhang et al, 2020). About 1-2 weeks later, the Runco Creativity Assessment Battery was administered to students during a 40-min session.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Positive psychological factors such as L2 grit, well-being, and self-efficacy were found to mediate the association between teacher-learner interpersonal relationships and learners' academic success [34]. Furthermore, researchers have also revealed the impact of students' perceived EFL teacher support on their academic achievement [11,35]. Chen and Chen [11] investigated different sources of social support (i.e., parents, teachers, and peers) on students' EFL academic achievement.…”
Section: Efl Teacher Support and Academic Achievementmentioning
confidence: 99%
“…EFL teachers are so influential that they can affect learners' personality traits, for instance, enhancing their ability to adapt effectively to challenges and difficulties, by sustaining a close relationship with them [9]. EFL teacher support, a multidimensional construct involving academic, instrumental, and emotional support [10], has been gradually revealed to exert a strong influence on students' personality development (e.g., academic buoyancy) and academic achievement [9,[11][12][13]. However, it remains unclear how different dimensions of EFL teacher support contribute to students' personality traits (e.g., academic buoyancy) and academic achievement.…”
Section: Introductionmentioning
confidence: 99%